Resin composition and molded article
Patent Information
- Application Number
- JP2020546511
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-04
- Filing Date
- 2020-08-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-08-27
AI Technical Summary
【0027】 本発明の樹脂組成物は、射出成形により複雑形状の部材に対する成形性が高いことに加えて、得られる成形品は曲げ弾性率および衝撃特性に優れる。
Smart Images

Figure 0007643041000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition containing carbon fibers that is suitable for injection molding, and which has a high flexural modulus and can be used to mold parts having complex shapes. [Background technology]
[0002] Carbon fiber composite materials, especially carbon fiber reinforced plastics, have been widely used in recent years as lightweight materials to replace components that have traditionally been made of light metals such as aluminum, due to their excellent mechanical properties. However, in order to achieve excellent mechanical properties, carbon fiber reinforced plastics are often used in the form of continuous or discontinuous fibers with a length of several mm or more, which poses the problem of difficulty in forming them into complex shapes. On the other hand, when injection molding, which has excellent formability for forming complex shapes, is applied to thermoplastic resins containing carbon fibers, the flexural modulus of the molded product is generally low, and the mechanical properties are not satisfactory for replacing light metals.
[0003] The most common ways to increase the flexural modulus of injection-molded products made from thermoplastic resins containing carbon fiber are to increase the carbon fiber content, to mold the products so that the carbon fibers remain long, and to increase the tensile modulus of the carbon fibers. Since these methods produce almost independent effects, each method is being investigated. [Prior art documents] [Patent documents]
[0004] In a method for increasing the tensile modulus of carbon fiber, there are examples in which a variety with a high tensile modulus is simply selected from commercially available carbon fibers. For example, by combining carbon fiber with a tensile modulus of 295 to 390 GPa with a specific aromatic amide, the flexural modulus of a molded product is increased to 39 GPa when the carbon fiber content is 40 mass% (Patent Document 1).
[0005] Also, a method has been proposed for increasing the tensile modulus of carbon fiber from the general-purpose 240 GPa to 290 GPa in combination with a specific polyamide resin (Patent Document 2).
[0006] In addition, by using polyphenylene sulfide resin and carbon fibers with a tensile modulus of elasticity of 390 to 450 GPa, the flexural modulus of the molded product is improved to 37 GPa when the carbon fiber content is 31 mass % (Patent Document 3).
[0007] Also, a technique has been proposed in which pitch-based carbon fibers having a tensile modulus of 860 GPa are used in combination with polyacrylonitrile-based carbon fibers (Patent Document 4). [Patent Document 1] JP 2006-1965 A [Patent Document 2] JP 2018-145292 A [Patent Document 3] JP 2017-190426 A [Patent Document 4] JP 2019-26808 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, the techniques proposed in the above-mentioned patent documents have the following problems.
[0009] In Patent Document 1, the effect of improving the flexural modulus of the molded product was observed, but the flexural modulus of the molded product was 32 GPa when using a general-purpose carbon fiber with a tensile modulus of 240 GPa, and the flexural modulus of the molded product was only improved by 1.2 times even if the tensile modulus of the carbon fiber was increased by 1.6 times, so the effect was extremely small. Also, when carbon fiber with a tensile modulus of 375 GPa was used, the crystallization parameter by Raman spectroscopy was small, that is, the carbonization temperature was high, and the single fiber diameter was small, so the flexural modulus of the molded product was 39 GPa, and the effect was small.
[0010] In Patent Document 2, when the carbon fiber content is 45 mass %, the flexural modulus of the molded article can be improved only to 33 to 35 GPa.
[0011] In Patent Document 3, the crystallization parameter measured by Raman spectroscopy is small, i.e., the carbonization temperature is high, and the single fiber diameter is small. Perhaps this is because the bending modulus of the molded article was not satisfactory not only when the carbon fiber content was 31% by mass, but also when the carbon fiber content was increased to 56% by mass.
[0012] In Patent Document 4, even when only pitch-based carbon fibers with a high tensile modulus were used, the flexural modulus of the molded product was at most 29 GPa, which was not a satisfactory result.
[0013] As described above, in the prior art, although there was an idea of using general-purpose carbon fibers having a high tensile modulus, there was no suggestion whatsoever about carbon fibers suitable for injection molding. [Means for solving the problem]
[0014] In order to solve the above problems, the resin composition of the present invention has any one of the following configurations. A resin composition containing carbon fiber and a thermoplastic resin, the carbon fiber has a single fiber diameter of 6.0 μm or more, a tensile modulus E of 350 to 500 GPa, the tensile modulus E (GPa) and the loop breaking load A (N) satisfy the relationship of formula (1), the thermoplastic resin is at least one thermoplastic resin selected from the group consisting of polyolefin, polyamide, polyester, polycarbonate, and polyarylene sulfide, and the mass content Wf of the carbon fiber is 15 to 55%. The carbon fiber is made of a carbon fiber bundle having a filament count of 3,000 to 60,000, and the twist angle of the surface layer of the carbon fiber bundle is 2.0 to 30.5°. A resin composition (hereinafter, the first aspect), A≧-0.0017×E+1.02...Equation (1), or A resin composition containing carbon fiber and a thermoplastic resin, the carbon fiber has a single fiber diameter of 6.0 μm or more, a crystallization parameter Iv / Ig determined by Raman spectroscopy is 0.65 or less, the crystallization parameter Iv / Ig and the tensile modulus E (GPa) satisfy the relationship of formula (2), the thermoplastic resin is at least one thermoplastic resin selected from the group consisting of polyolefins, polyamides, polyesters, polycarbonates, and polyarylene sulfides, and the mass content Wf of the carbon fiber is 15 to 55%. The carbon fiber is made of a carbon fiber bundle having a filament count of 3,000 to 60,000, and the twist angle of the surface layer of the carbon fiber bundle is 2.0 to 30.5°. A resin composition (hereinafter, the second aspect), E ≥ 290 × (Iv / Ig) -0.23 ...Equation (2) or In a resin composition containing carbon fiber and a thermoplastic resin, the single fiber diameter of the carbon fiber is 6.0 μm or more, the thermoplastic resin is at least one thermoplastic resin selected from the group consisting of polyolefin, polyamide, polyester, polycarbonate, and polyarylene sulfide, the mass content Wf of the carbon fiber is 15 to 55%, and the flexural modulus FM (GPa) of the resin composition, the mass content Wf (%) of the carbon fiber in the resin composition, and the tensile modulus E (GPa) of the carbon fiber satisfy the relationships of formulas (5) and (6). The carbon fiber is made of a carbon fiber bundle having a filament count of 3,000 to 60,000, and the twist angle of the surface layer of the carbon fiber bundle is 2.0 to 30.5°. A resin composition (hereinafter, the third embodiment).
[0015] FM / Wf 0.5 >6.8...Equation (5) FM / Wf 0.5 >0.01×E+3.00...Equation (6).
[0016] The molded article of the present invention has the following configuration. A molded article obtained by molding the above resin composition.
[0017] In the resin composition according to the second aspect of the present invention, the crystallization parameter Iv / Ig of the carbon fiber determined by Raman spectroscopy is preferably 0.40 or more.
[0018] In the resin composition of the first or second aspect of the present invention, it is preferable that the single fiber compressive strength Fc (GPa) and crystallite size Lc (nm) of the carbon fiber single fiber composite measured by the compression fragmentation method satisfy the relationship of formula (3).
[0019] Fc≧1.3×10 / Lc-0.2 Formula (3) The resin composition according to the first or second aspect of the present invention has a crystal orientation degree π of the carbon fiber. 002 is 80.0-95.0%, the crystallite size Lc is 2.2-3.5 nm, and the crystallite size Lc (nm) and the degree of crystal orientation π 002 It is preferable that (%) satisfies the relationship of formula (4).
[0020] π 002 ≧4.0×Lc+73.2 Formula (4) In the resin composition according to the first or second aspect of the present invention, which is obtained by melt-kneading carbon fibers and a thermoplastic resin, it is preferable that the length of the carbon fibers before melt-kneading is 100 mm or more.
[0021] In the resin composition according to the first or second aspect of the present invention, the carbon fiber preferably has a heat loss rate at 450° C. of 0.15% or less.
[0022] In the resin composition according to the first or second embodiment of the present invention, the carbon fiber is composed of a carbon fiber bundle having a filament count of 3,000 to 60,000, and the twist angle of the surface layer of the carbon fiber bundle is 2.0 to 30.5°. do.
[0023] In the resin composition according to the first or second aspect of the present invention, the single fiber diameter of the carbon fiber is 6.0 μm or more. do.
[0024] In the resin composition according to the first or second aspect of the present invention, the carbon fiber preferably has a single fiber diameter of 6.5 to 8.5 μm.
[0025] In the resin composition according to the third aspect of the present invention, the mass content Wf of the carbon fiber is 15 to 55%. do.
[0026] In the resin composition according to the third aspect of the present invention, the carbon fiber preferably has a flexural modulus FM of 41 to 55 GPa. Effect of the Invention
[0027] The resin composition of the present invention has high moldability by injection molding into parts with complex shapes, and the obtained molded articles have excellent flexural modulus and impact properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The resin composition of the present invention contains carbon fibers and a thermoplastic resin.
[0029] First, the carbon fiber used in the present invention will be described.
[0030] The carbon fiber used in the present invention has a tensile modulus E of 350 to 500 GPa. The higher the tensile modulus of the carbon fiber, the higher the flexural modulus of the injection molded product tends to be. If the tensile modulus is less than 350 GPa, the flexural modulus of the injection molded product cannot be increased. If the tensile modulus of the carbon fiber exceeds 500 GPa, the effect of improving the flexural modulus of the injection molded product is weakened. The lower limit of the tensile modulus E of the carbon fiber is preferably 370 GPa or more, more preferably 380 GPa or more. The tensile modulus of the carbon fiber is evaluated according to the tensile test of the resin-impregnated strand described in JIS R7608:2004. The details of the evaluation method of the strand modulus will be described later.
[0031] The carbon fiber used in the resin composition according to the first embodiment of the present invention is a carbon fiber whose tensile modulus E (GPa) and loop breaking load A (N) satisfy the relationship of formula (1).
[0032] A≧-0.0017×E+1.02...Equation (1).
[0033] The constant term in formula (1) is preferably 1.04, more preferably 1.06. The loop breaking load corresponds to the load at which a single fiber breaks when it is bent into a loop, and is evaluated by the method described below. Usually, when the tensile modulus is increased, the loop breaking load tends to decrease. If the loop breaking load is low, the carbon fiber is easily broken by the force in the bending direction during injection molding, and the fiber length is shortened, so that the effect of improving the flexural modulus of the injection molded product is reduced. In the present invention, unless a specific carbon fiber that satisfies the relationship of formula (1) above, in which the loop breaking load is high even if the tensile modulus of the carbon fiber is increased, is used, the flexural modulus of the injection molded product cannot be effectively increased.
[0034] The carbon fiber used in the resin composition according to the second embodiment of the present invention is a carbon fiber having a crystallization parameter Iv / Ig of 0.65 or less as determined by Raman spectroscopy. The crystallization parameter Iv / Ig as determined by Raman spectroscopy in the present invention is evaluated from the analysis of a Raman spectrum obtained from a cross section of a single fiber of the carbon fiber. The detailed evaluation method will be described later. Such a Raman spectrum has a peak at 1580 cm -1 Nearby G band, 1360cm -1 D band nearby, 1480cm -1 A valley appears between these bands near the peak intensity of the G band, Ig, 1480 cm -1 The part with the weakest spectral intensity around the center is defined as Iv, and the ratio is an index showing the progress of crystallization in the internal structure of the carbon fiber. For commercially available carbon fibers, those with a tensile modulus of elasticity of around 380 GPa have an Iv / Ig of less than 0.2, and those with a tensile modulus of elasticity of 230 to 290 GPa have an Iv / Ig of 0.70 or more. When the Iv / Ig is 0.65 or less, crystallization has progressed sufficiently, and the tensile modulus of elasticity of the carbon fiber is high.
[0035] The crystallization parameter Iv / Ig can be adjusted by the maximum carbonization temperature during carbon fiber production. The upper limit of the crystallization parameter Iv / Ig is preferably 0.60, and more preferably 0.55.
[0036] The carbon fiber used in the resin composition according to the second embodiment of the present invention is a carbon fiber in which the crystallization parameter Iv / Ig and the tensile modulus E (GPa) satisfy the relationship shown in formula (2).
[0037] E ≥ 290 × (Iv / Ig) -0.23 ...Equation (2) The smaller the crystallization parameter Iv / Ig, the more advanced the crystallization and the higher the tensile modulus of the carbon fiber. As a general trend, for example, in "TORAYCA" (registered trademark) T700S-24000-50E manufactured by Toray Industries, Inc., Iv / Ig is 0.91 and the tensile modulus is 230 GPa, in "TORAYCA" (registered trademark) M40J-12000-50E manufactured by Toray Industries, Inc., Iv / Ig is 0.18 and the tensile modulus is 377 GPa, and in "TORAYCA" (registered trademark) M55J-6000-50E manufactured by Toray Industries, Inc., Iv / Ig is 0.05 and the tensile modulus is 536 GPa. As such, the smaller the Iv / Ig, the more the tensile modulus tends to increase at an accelerated rate, and a power relationship is generally observed between these two parameters. The more the crystallization progresses, the more likely the carbon fiber is to break due to a bending force during injection molding. Therefore, the inventors have conducted research and found that carbon fibers that satisfy formula (2) can maintain a high tensile modulus and resistance to breaking at a high level. The physical meaning of formula (2) is that it is better to use carbon fibers that are not highly crystallized compared to their high tensile modulus. By using a specific carbon fiber that satisfies the relationship of formula (2), the bending modulus of the injection molded product can be effectively increased. From the viewpoint of further effectively increasing the bending modulus of the injection molded product, it is preferable to set the coefficient of formula (2) to 300 instead of 290.
[0038] In the carbon fiber used in the present invention, the lower limit of the crystallization parameter Iv / Ig is preferably 0.25 or more, more preferably 0.30 or more, and even more preferably 0.40 or more. When the crystallization parameter Iv / Ig is 0.25 or more, the tensile modulus of the carbon fiber itself is not at an extremely high level, but the resistance of the carbon fiber to breaking during injection molding is at least to a certain level, and as a result, the flexural modulus of the injection molded product is likely to be high relative to the tensile modulus of the carbon fiber.
[0039] In the carbon fiber used in the present invention, the crystallite size Lc is preferably 2.2 to 3.5 nm, more preferably 2.4 to 3.3 nm, and even more preferably 2.6 to 3.1 nm. The crystallite size is an index representing the thickness of the crystallite in the c-axis direction present in the carbon fiber, and corresponds to the amount of heat treatment during carbonization. The more heat treatment is performed, the higher the tensile modulus tends to be, and at the same time, the more likely the carbon fiber is to break during injection molding. If the crystallite size Lc is within the above range, the balance between the tensile modulus and the ease of breaking of the carbon fiber is excellent. The crystallite size Lc is evaluated by wide-angle X-ray diffraction of the carbon fiber. A detailed evaluation method will be described later.
[0040] In the carbon fiber used in the present invention, the crystal orientation degree π 002 is preferably 80.0 to 95.0%, more preferably 80.0 to 90.0%, and further preferably 82.0 to 90.0%. 002 is an index that indicates the orientation angle of the crystallites present in carbon fiber based on the fiber axis. Like the crystallite size, it is evaluated by wide-angle X-ray diffraction. Detailed evaluation methods will be described later. If the crystal orientation degree is 80.0% or more, the carbon fiber is less likely to break during injection molding, and if the crystal orientation degree is 95.0% or less, the tensile modulus of the carbon fiber is likely to be satisfactory.
[0041] The carbon fibers preferably used in the present invention have a crystallite size Lc (nm) and a single fiber compressive strength Fc (GPa) of a single fiber composite measured by a compression fragmentation method, which falls within the range of the following formula (3).
[0042] Fc≧1.3×10 / Lc-0.2 (3).
[0043] The right side of the formula (3) of the carbon fiber used in the present invention is more preferably 1.3×10 / Lc+0.1, and even more preferably 1.3×10 / Lc+0.5. It is generally known that the single fiber compressive strength tends to decrease as the crystallite size of the carbon fiber increases. In contrast, the flexural modulus of the injection molded product can be effectively increased by using carbon fiber with a single fiber compressive strength higher than the conventional level expected from the crystallite size. Carbon fiber can obtain a satisfactory value of the flexural modulus of the injection molded product by satisfying formula (3). The compression fragmentation method of the single fiber composite used in the present invention is a method for examining the single fiber compressive strength of the carbon fiber by applying a compressive strain stepwise to a carbon fiber reinforced composite material (single fiber composite) in which a single fiber of carbon fiber is embedded in a resin, and counting the number of fiber breaks at each compressive strain. In order to convert the single fiber composite compressive strain at the time of fiber breakage into the single fiber compressive strength, it is necessary to consider the difference between the single fiber composite compressive strain and the fiber compressive strain, and the nonlinearity of the elastic modulus at each fiber compressive strain. Therefore, the single fiber compressive stress is calculated by dividing the stress-strain (SS) curve obtained from the strand tensile test (details will be described later) into a quadratic function y=ax in the range of 0≦y≦3, with the X-axis representing strain and the Y-axis representing stress. 2 +bx+c, and the fitting line is extended to the compression strain side to determine the strength. The single fiber compressive strength is the single fiber compressive stress at which the number of breaks exceeds 1 per 10 mm.
[0044] In the carbon fiber used in the present invention, the crystallite size Lc (nm) and the crystal orientation degree π 00 It is preferable that 2(%) satisfies the relationship of formula (4).
[0045] π 002 ≧4.0×Lc+73.2...Equation (4).
[0046] According to the inventors' investigation, the crystal orientation degree π 002Equation (4) shows the upper limit of this relationship empirically based on known carbon fiber data. Usually, the larger the crystallite size Lc, the higher the tensile modulus of the carbon fiber, but the loop breaking load and single fiber compressive strength tend to decrease. In addition, the degree of crystal orientation π 002 The degree of crystal orientation strongly influences the bending modulus of the injection molded product, and the higher the degree of crystal orientation, the higher the bending modulus of the injection molded product. 002 The fact that the relationship of formula (4) is satisfied means that the degree of crystal orientation π 002 This means that the tensile modulus of elasticity of the carbon fiber is large, and when the tensile modulus of elasticity of the carbon fiber is high, the flexural modulus of the injection molded product can be effectively increased, which is of great industrial value. In the present invention, the constant term in formula (4) is more preferably 73.5, and further preferably 74.0.
[0047] The carbon fiber used in the present invention has a heat loss rate at 450°C of preferably 0.15% or less, more preferably 0.10% or less, and even more preferably 0.07% or less. In the present invention, the heat loss rate at 450°C is measured in detail below, but refers to the mass change rate before and after a certain amount of the carbon fiber to be measured is weighed and heated for 15 minutes in an oven in an inert gas atmosphere set at a temperature of 450°C. Carbon fibers with a low heat loss rate under such conditions contain a small amount of components that thermally decompose when exposed to high temperatures, such as sizing agents, and when the heat loss rate is 0.15% or less, the dispersion of the carbon fiber in the resin composition is excellent, so that the flexural modulus of the injection molded product tends to be high.
[0048] The carbon fiber used in the present invention is a resin composition obtained by melt-kneading carbon fiber and a thermoplastic resin, and the length of the carbon fiber before melt-kneading is preferably 100 mm or more, more preferably 1000 mm or more. During injection molding, carbon fiber cut into several mm pieces, generally called chopped carbon fiber, is often used because of ease of handling. When the length of the carbon fiber is small, not only does one process of processing the continuous fiber into chopped carbon fiber increase, but the flexural modulus of the injection molded product tends to decrease, which is not preferable. Therefore, it is more preferable that the carbon fiber used in injection molding is a continuous fiber, and in the present invention, a carbon fiber that is continuous for 1 m or more is essentially a continuous fiber.
[0049] The carbon fiber used in the present invention is in the form of a carbon fiber bundle having 3,000 to 60,000 filaments, and the twist angle of the surface layer of the carbon fiber bundle is but 2.0~30.5° , good Preferably, the angle is 4.8 to 30.5°. twist Preferably, it is 4.8 to 24.0°. The twist angle of the surface layer of the carbon fiber bundle is the angle that the fiber axis direction of the single fiber present in the outermost layer of the carbon fiber bundle forms with the long axis direction of the carbon fiber bundle as a bundle, and may be directly observed, but can be calculated more accurately from the number of twists, the number of filaments, and the single fiber diameter as described below. If the twist angle is controlled within the above range, it is preferable because the carbon fibers can be fed into the injection molding machine with good bundling properties, and the fiber length contained in the injection molded product can be increased because the carbon fibers can be fed into the injection molding machine with long fiber length.
[0050] The carbon fibers used in the present invention have a single fiber diameter but 6.0 μm or more, good Preferably, it is 6.5 μm or more. twistPreferably, it is 6.9 μm or more. The larger the single fiber diameter, the more likely the fiber will remain long during injection molding and the more likely the flexural modulus will increase, and when the single fiber diameter is 6.0 μm or more, the flexural modulus of the injection molded product is more likely to increase. In the present invention, there is no particular limit to the upper limit of the single fiber diameter, but if it is too large, the tensile modulus of the carbon fiber may decrease, so about 15 μm may be considered as the upper limit for the time being. In addition, if it is 8.5 μm or less, the balance between the tensile modulus of the carbon fiber and the productivity is good, and it is easy to increase the industrial value. The method of evaluating the single fiber diameter will be described later, but it may be calculated from the specific gravity, basis weight, and number of filaments of the fiber bundle, or it may be evaluated by scanning electron microscope observation. As long as the evaluation device used is properly calibrated, the same results can be obtained regardless of the method of evaluation. When evaluating by scanning electron microscope observation, if the cross-sectional shape of the single fiber is not a perfect circle, it is substituted with the circle equivalent diameter. The circle equivalent diameter refers to the diameter of a perfect circle having a cross-sectional area equal to the actually measured cross-sectional area of the single fiber.
[0051] The thermoplastic resin used in the present invention is preferably at least one thermoplastic resin selected from the group consisting of polyolefin, polyamide, polyester, polycarbonate and polyarylene sulfide, and from the viewpoint of the flexural modulus of the obtained molded article, polyamide and polyarylene sulfide are more preferable, and polyarylene sulfide is particularly more preferable. Since the mechanical properties such as the flexural modulus of the obtained molded article can be improved without restrictions on the type of thermoplastic resin by combining with the carbon fiber used in the present invention, the thermoplastic resin can be selected widely, but the effect of the present invention can be easily obtained by selecting a thermoplastic resin that is easy to improve the mechanical properties of the molded article, specifically a thermoplastic resin that exhibits high tensile yield stress.
[0052] The polyolefin may be a homopolymer of propylene or a copolymer of propylene with at least one α-olefin, conjugated diene, non-conjugated diene, or the like.
[0053] The polyamide may be a polymer having a main chain formed by repeating amide groups, such as aliphatic polyamides such as polyamide 6, polyamide 66, polyamide 11, polyamide 610, and polyamide 612, or aromatic polyamides such as polyamide 6T. A mixture of these or a copolymer of multiple types of polyamides may also be used.
[0054] The polyarylene sulfide may include, as its constituent units, p-phenylene sulfide units, m-phenylene sulfide units, o-phenylene sulfide units, phenylene sulfone units, phenylene sulfide ketone units, phenylene sulfide ether units, diphenylene sulfide units, phenylene sulfide units containing a substituent, and phenylene sulfide units containing a branched structure, and poly-p-phenylene sulfide is particularly preferred.
[0055] The resin composition of the present invention may contain additives within the range that does not impair the effects of the present invention. Specific examples of additives include antioxidants, heat stabilizers, weathering agents, release agents, lubricants, pigments, dyes, plasticizers, antistatic agents, flame retardants, and petroleum resins used in injection molding. Petroleum resins are polymerized hydrocarbon compounds produced as by-products during the thermal decomposition of naphtha, and include C9 petroleum resins obtained by polymerizing C9 fractions consisting of aromatic hydrocarbons, C5 petroleum resins obtained by polymerizing C5 fractions consisting of aliphatic hydrocarbons, and C5-C9 copolymerized petroleum resins obtained by copolymerization using C9 fractions and C5 fractions as raw materials, as well as modified petroleum resins obtained by modifying these petroleum resins with maleic anhydride, maleic acid, fumaric acid, (meth)acrylic acid, phenol, etc.
[0056] The first preferred embodiment of the method for producing the resin composition of the present invention is to produce the resin composition by mixing the above-mentioned components simultaneously or in any order using a mixer such as a tumbler, a V-type blender, a Nauter mixer, a Banbury mixer, a kneading roll, or an extruder, and more preferably melt-kneading using a twin-screw extruder. As the extruder, one having a vent capable of degassing the moisture in the raw material and the volatile gas generated from the melt-kneaded resin is preferably used. A vacuum pump is preferably installed from the vent to efficiently discharge the generated moisture and volatile gas to the outside of the extruder. In addition, a screen for removing foreign matter mixed in the extrusion raw material can be installed in a zone before the extruder die section to remove foreign matter from the resin composition. Examples of such a screen include a wire net, a screen changer, and a sintered metal plate.
[0057] At this time, it is preferable to continuously supply the carbon fibers, and it is more preferable to supply the carbon fibers after melt-kneading the thermoplastic resin.
[0058] A second preferred embodiment of the method for producing a resin composition of the present invention is a method in which the petroleum resin is first attached to the carbon fiber, and then the thermoplastic resin is bonded thereto. The petroleum resin attachment step can use a known manufacturing method such as adding an oil agent, a sizing agent, and a matrix resin to the fiber bundle, but a more specific example is a method in which a film of molten petroleum resin of a certain thickness is coated on the surface of a heated rotating roll, and the carbon fiber is run while being attached to the surface of the roll, thereby attaching a predetermined amount of petroleum resin per unit length of the carbon fiber. Coating of the petroleum resin on the roll surface can be realized by applying the concept of a known coating device such as a reverse roll, a forward rotating roll, a kiss roll, a spray, a curtain, or an extrusion. In the step of attaching the petroleum resin to the carbon fiber, the petroleum resin is impregnated into the spaces between the single fibers of the carbon fiber bundle by applying tension with a roll or a bar to the carbon fiber to which the petroleum resin is attached, repeating widening and focusing, and applying pressure or vibration to the carbon fiber to which the petroleum resin is attached at a temperature at which the petroleum resin melts. A more specific example is a method in which the carbon fibers are passed through the surfaces of a plurality of heated rolls or bars so as to come into contact with each other.
[0059] Furthermore, the petroleum resin-attached carbon fiber, which is made of carbon fiber and petroleum resin, comes into contact with the above-mentioned thermoplastic resin to form a resin composition. In the step of arranging the thermoplastic resin, the molten thermoplastic resin is arranged so as to come into contact with the petroleum resin-attached carbon fiber. More specifically, there can be mentioned a method of continuously arranging the petroleum resin-attached carbon fiber so as to coat it with the thermoplastic resin using an extruder and a coating die for electric wire coating, or a method of arranging a molten film-like thermoplastic resin using an extruder and a T-die from one or both sides of the petroleum resin-attached carbon fiber flattened with a roll or the like, and integrating it with a roll or the like.
[0060] After the carbon fibers are integrated with the thermoplastic resin in the first or second preferred embodiment described above, they may be cut into a fixed length of, for example, 1 to 50 mm using a device such as a pelletizer or strand cutter. This cutting step may be continuously performed after the placement step of the thermoplastic resin. If the molding material is flat or in a sheet form, it may be slit into elongated pieces and then cut. A sheet pelletizer that simultaneously performs slitting and cutting may be used.
[0061] The resin composition of the present invention preferably has a flexural modulus FM of 41 to 55 GPa, more preferably 44 to 55 GPa. The flexural modulus is measured according to ISO 178 and is a major factor of rigidity that indicates the resistance of a component to bending. The greater the flexural modulus, the less the resin composition used can be maintained, leading to a reduction in the weight of the component. If the flexural modulus is 41 GPa or more, the properties are comparable to those of magnesium alloys, which are representative of lightweight metals, and this is a satisfactory result. Although the higher the flexural modulus, the better, if it is 55 GPa or less, it is sufficient to replace magnesium alloys. The key to controlling the flexural modulus within the above range is to use the above-mentioned carbon fibers.
[0062] The resin composition of the present invention preferably contains 15 to 55 mass %, more preferably 25 to 50 mass % of carbon fiber. The mass content Wf of carbon fiber can be adjusted depending on the application and the target physical properties, and if only the bending modulus of the resin composition is considered, it is preferable to increase the mass content. If the mass content of carbon fiber is 15 mass % or more, the bending modulus of the resin composition is high, and if it is 55 mass % or less, the moldability during injection can be maintained. The mass content of carbon fiber can be calculated from the ratio of the input carbon fiber to the thermoplastic resin and other added components.
[0063] In the resin composition of the present invention containing carbon fiber and a thermoplastic resin, the flexural modulus of the resin composition F (GPa), the mass content Wf (%) of the carbon fiber in the resin composition, and the tensile modulus E (GPa) of the carbon fiber satisfy the relationships of formulas (5) and (6).
[0064] FM / Wf 0.5 >6.8...Equation (5) FM / Wf 0.5 >0.01×E+3.00...Equation (6).
[0065] The flexural modulus depends on the mass content Wf of the carbon fiber, but is not proportional to Wf, so it is empirically normalized to the 0.5 power of Wf. FM / Wf 0.5 When the relationship of formula (5) is not satisfied, the effect of improving the flexural modulus of the resin composition relative to the mass content of carbon fiber cannot be expected. Furthermore, when the relationship of formula (6) is not satisfied, the flexural modulus of the resin composition cannot be effectively increased even if the tensile modulus E of the carbon fiber is increased. The present inventors have confirmed that the resin compositions described in the examples of the above-mentioned Patent Documents 1 to 3 do not satisfy formulas (5) and (6). In order to control the formulas (5) and (6) to be satisfied, it is necessary to select the carbon fiber used in the present invention.
[0066] The number average fiber length of the carbon fibers in the molded product obtained by the resin composition of the present invention is preferably 0.3 to 2 mm, more preferably 0.4 to 1 mm. By setting it in this range, the effect of the carbon fibers reinforcing the thermoplastic resin in the molded product can be enhanced, and the mechanical properties of the molded product can be sufficiently improved. Here, a method for measuring the number average fiber length in the molded product will be described. As a method for measuring the number average fiber length of the carbon fibers contained in the molded product, for example, there is a method in which the resin components contained in the molded product are removed by a dissolution method or a burn-off method, the remaining carbon fibers are filtered out, and then the number average fiber length is measured by observation with a microscope. For the measurement, 400 carbon fibers are randomly selected, their lengths are measured to the nearest 1 μm with an optical microscope, and the number average fiber length is calculated by dividing the total fiber length by the number of fibers. In order to control the number average fiber length to the above range, it can be achieved by using the carbon fibers that are not easily broken during injection molding as described above.
[0067] <Tensile modulus of carbon fiber> The tensile elastic modulus of carbon fiber is determined according to the following procedure in accordance with the resin-impregnated strand test method of JIS R7608 (2004). However, when the fiber bundle of carbon fiber has twist, it is untwisted by applying the same number of reverse twists as the number of twists and then evaluated. As the resin formulation, "Celloxide" (registered trademark) 2021P (manufactured by Daicel Chemical Industries, Ltd.) / boron trifluoride monoethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) / acetone = 100 / 3 / 4 (parts by mass) is used, and as the curing conditions, normal pressure, a temperature of 125 °C, and a time of 30 minutes are used. Ten strands of the carbon fiber bundle are measured, and the average value is taken as the strand strength and the strand elastic modulus. Note that the strain range for calculating the strand elastic modulus is 0.1 to 0.6%. <Crystallization parameter Iv / Ig by Raman spectroscopy> The resin composition is resin-embedded and polished to expose the cross-section of a single carbon fiber. In order to avoid the influence of polishing damage on the Raman spectrum, finish polishing is performed using an abrasive of about 0.05 μm diameter at the final stage of polishing. Five points of the cross-section of a single carbon fiber are randomly selected, and the Raman spectrum is measured using a microscopic Raman spectrometer. The measurement points are near the center of each single fiber cross-section. The excitation wavelength is 532 nm, the laser intensity is 1 mW, and the measurement range is 900 to 2000 cm -1 , the laser beam is narrowed to a diameter of 2 μm, and the measurement time is integrated three times for 60 seconds each. The baseline of the obtained spectrum is offset using a linear function so that the scattering intensities at 1000 cm -1 and 1800 cm -1 become 0, and the crystallization parameter Iv / Ig is calculated with the height of the G band as Ig and the height of the valley bottom near 1480 cm -1 as Iv. To minimize the influence of errors, when determining Ig, the range of about ±10 cm -1 from near the visually observed peak of the G band is approximated by least squares using a quadratic function, and the peak top intensity of the fitting function is taken as Ig. For Iv as well, Iv is determined in the same manner for the vicinity of the valley near 1480 cm -1 . In the present invention, the average value of Iv / Ig for five points is used.
[0068] In the examples, "EpoKwick" (registered trademark) FC (manufactured by Buehler) was used as the embedding resin, and "AutoMet" (registered trademark) 250Pro (manufactured by Buehler) was used as the polishing device. The polishing was performed by using polishing pads of #320, #500, and #700 for rough polishing, and then using "MasterTex" (manufactured by Buehler) as the polishing cloth and a 0.05 μm diameter alumina suspension as the polishing agent. In order to confirm the presence or absence of polishing damage, when the resin composition is embedded in resin, "TORAYCA" (registered trademark) M40J-12000-50E manufactured by Toray Industries, Inc. is always used as a blank and is simultaneously embedded in a direction in which the fiber axis is perpendicular to the polished surface. If Iv / Ig evaluated by the above method for such M40J is 0.18±0.02, the polishing damage has been minimized, and if not, the polishing is redone.
[0069] <Average single fiber diameter of carbon fibers> The cross section of the single fiber of the carbon fiber to be evaluated is observed with a scanning electron microscope, and the cross-sectional area is evaluated. The diameter of a perfect circle having the same cross-sectional area is calculated and used as the single fiber diameter. The N number for calculating the single fiber diameter is 50, and the average value is used. The accelerating voltage is 5 keV.
[0070] In the present invention, a scanning electron microscope (SEM) S-4800 manufactured by Hitachi High-Technologies Corporation can be used as the scanning electron microscope.
[0071] <Twist angle of the surface layer of carbon fiber bundle> A guide bar is placed at a height of 60 cm from the horizontal plane, and an arbitrary position of the carbon fiber bundle is attached to the guide bar with tape to form a fixed end, and then the carbon fiber bundle is cut at a position 50 cm away from the fixed end to form a free end. The free end is sealed by being sandwiched between tape to prevent it from unraveling into single fiber units. In order to eliminate temporary twists other than semi-permanent twists or twists that return over time, the free end is rotated while counting the number of rotations, and the number of rotations n (turns) until the twist is completely untwisted is recorded. The remaining twist number is calculated using the following formula. The average of the above measurements performed three times is the remaining twist number in the present invention.
[0072] Remaining twist (turns / m) = n (turns) / 0.5 (m).
[0073] The diameter (μm) of the entire carbon fiber bundle is calculated from the single fiber diameter (μm) and the number of filaments according to the following formula, and then the twist angle (°) of the surface layer of the carbon fiber bundle is calculated using the twist number (turns / m) according to the following formula.
[0074] Total diameter of carbon fiber bundle (μm) = {(single fiber diameter) 2 × number of filaments} 0.5 Twist angle of the surface layer of the carbon fiber bundle (°) = atan(diameter of the entire fiber bundle × 10 -6 ×π×number of twists).
[0075] <Loop breaking load> A single fiber with a length of about 10 cm is placed on a slide glass, 1 to 2 drops of glycerin are dropped on the center, and both ends of the single fiber are lightly twisted in the circumferential direction of the fiber to create a loop in the center of the single fiber, and a cover glass is placed on top of it. This is placed on the stage of a microscope, and video is recorded under conditions of a total magnification of 100 times and a frame rate of 15 frames / second. While adjusting the stage each time so that the loop does not leave the field of view, both ends of the looped fiber are pressed toward the slide glass with fingers while pulling in the opposite direction at a constant speed, applying strain until the single fiber breaks. The frame immediately before break is identified by frame advance, and the width W of the loop immediately before break is measured by image analysis. d / W is calculated by dividing the single fiber diameter d by W. The number of tests is 20, and the loop strength E × d / W is calculated by multiplying the average value of d / W by the tensile modulus E. Furthermore, the cross-sectional area πd calculated from the single fiber diameter is calculated. 2 Multiply by / 4, πE×d 3 / 4W is the loop breaking load.
[0076] <Single fiber compressive strength of carbon fiber> The measurement of single fiber compressive strength of a single fiber composite by the compression fragmentation method is carried out according to the following steps (i) to (v).
[0077] (i) Preparation of resin 190 parts by mass of bisphenol A type epoxy resin compound "Epotohto" (registered trademark) YD-128 (manufactured by Nippon Steel Chemical Co., Ltd.) and 20.7 parts by mass of diethylenetriamine (manufactured by Wako Pure Chemical Industries, Ltd.) are placed in a container and stirred with a spatula, and then degassed using an automatic vacuum degassing apparatus.
[0078] (ii) Sampling of carbon fiber single fibers and fixing them to a mold A carbon fiber bundle with a length of about 20 cm is divided into approximately four equal parts, and single fibers are sampled in order from each of the four bundles. At this time, the entire bundle is sampled as evenly as possible. Next, double-sided tape is attached to both ends of a perforated mount, and the sampled single fiber is fixed to the perforated mount while applying a certain tension to the single fiber. Next, a glass plate with a polyester film "Lumirror" (registered trademark) (manufactured by Toray Industries, Inc.) attached thereto is prepared, and a 2 mm thick spacer is fixed on the film to adjust the thickness of the test piece. The perforated mount with the single fiber fixed thereto is placed on the spacer, and a glass plate with a similar film attached thereto is set on top of that with the side with the film attached facing down. At this time, in order to control the embedding depth of the fiber, a tape with a thickness of about 70 μm is attached to both ends of the film.
[0079] (iii) From resin casting to hardening The resin prepared in step (i) above is poured into the mold prepared in step (ii) above (the space surrounded by the spacer and film). The mold into which the resin has been poured is heated for 5 hours in an oven that has been preheated to 50°C, and then cooled to 30°C at a rate of 2.5°C / min. The mold is then demolded and cut to obtain a test piece measuring 2 cm x 7.5 cm x 0.2 cm. At this time, the test piece is cut so that the single fiber is located within a 0.5 cm width at the center of the test piece width.
[0080] (iv) Fiber embedment depth measurement The test piece obtained by the above step (iii) is subjected to measurement of the embedding depth of the fiber using a laser Raman spectrophotometer (JASCO Corporation NRS-3200) and a 532 nm notch filter. First, the laser is applied to the surface of the single fiber, and the stage height is adjusted so that the laser beam diameter is the smallest, and the height at that time is defined as A (μm). Next, the laser is applied to the surface of the test piece, and the stage height is adjusted so that the laser beam diameter is the smallest, and the height at that time is defined as B (μm). The embedding depth d (μm) of the fiber is calculated by the following formula using the refractive index of the resin, 1.732, measured using the above laser.
[0081] d = (A B ) × 1.732.
[0082] (v) Four-point bending test The test piece obtained by step (iii) above is subjected to compressive strain in four-point bending using a jig with outer indenters spaced 50 mm apart and inner indenters spaced 20 mm apart. Strain is applied stepwise in increments of 0.1%, the test piece is observed under a polarizing microscope, and the number of breaks in the central 5 mm area in the longitudinal direction of the test piece is measured. The number of fiber breaks (pieces / 10 mm) is determined as twice the measured number of breaks, and the compressive stress calculated from the compressive strain at which the average number of fiber breaks for 30 tests exceeds 1 piece / 10 mm is determined as the single fiber compressive strength. In addition, the single fiber composite strain ε (%) is measured using a strain gauge attached at a position approximately 5 mm away from the center of the test piece in the width direction. The final compressive strain ε of the carbon fiber single fiber is determined as follows: c is calculated using the following formula, taking into consideration the gauge factor κ of the strain gauge, the fiber embedment depth d (μm) measured in step (iv) above, and a residual strain of 0.14 (%).
[0083] ε c =ε×(2 / κ)×(1-d / 1000)-0.14.
[0084] <Weight loss rate of carbon fiber bundle at 450℃> The carbon fiber bundle to be evaluated is cut to a mass of 2.5 g, wound into a skein with a diameter of approximately 3 cm, and the mass before heat treatment, w0 (g), is weighed. Next, it is heated in an oven in a nitrogen atmosphere at 450°C for 15 minutes, and after cooling to room temperature in a desiccator, the mass after heating, w1 (g), is weighed. The heating weight loss rate at 450°C is calculated using the following formula. The evaluation is performed three times, and the average value is used.
[0085] Weight loss at 450℃ (%) = (w0-w1) / w0 × 100 (%).
[0086] <Crystallite size Lc and crystal orientation degree π of carbon fiber bundle 002 > The carbon fiber bundles to be measured are aligned and solidified using a collodion-alcohol solution to prepare a measurement sample in the shape of a square pillar 4 cm long and 1 mm on each side. The measurement sample is measured using a wide-angle X-ray diffraction device under the following conditions.
[0087] [1] Measurement of crystallite size Lc X-ray source: CuKα (tube voltage 40kV, tube current 30mA) Detector: Goniometer + Monochromator + Scintillation counter Scanning range: 2θ=10~40° Scanning mode: Step scan, step unit 0.02°, counting time 2 seconds.
[0088] In the obtained diffraction pattern, the half-width is determined for a peak appearing in the vicinity of 2θ=25 to 26°, and the crystallite size is calculated from this value using the following Scherrer formula.
[0089] Crystallite size (nm) = Kλ / β0cosθ B Where: K: 1.0, λ: 0.15418nm (X-ray wavelength) β0:(β E 2 -β1 2 ) 1 / 2 β E : Apparent half-width (measured value) rad, β1: 1.046×10 -2 rad θ B :Bragg diffraction angle.
[0090] [2] Crystal orientation degree π 002 Measurement The above crystal peak is scanned in the circumferential direction to obtain an intensity distribution, and the half-width is calculated using the following formula.
[0091] π 002 =(180-H) / 180 Where: H: Apparent half-width (deg) The above measurements are carried out three times, and the arithmetic averages are taken as the crystallite size and degree of crystal orientation of the carbon fiber bundle.
[0092] In the examples and comparative examples described later, an XRD-6100 manufactured by Shimadzu Corporation was used as the wide-angle X-ray diffraction device.
[0093] <Bending test of molded products> For ISO dumbbell test pieces, the bending strength is measured in accordance with ISO 178 (2010) using a three-point bending test jig (indenter radius 5 mm) with a support distance set to 64 mm and a test speed of 2 mm / min. The test pieces are left in a constant temperature and humidity room adjusted to a temperature of 23°C and 50% RH for 24 hours before being used for characteristic evaluation tests. Measurements are performed on n=6 molded products, and the bending strength is calculated as the average value.
[0094] In the examples and comparative examples described later, an "Instron" (registered trademark) universal testing machine Model 4201 (manufactured by Instron Corporation) was used as the testing machine.
[0095] <Charpy impact strength of molded products> The parallel part of the ISO dumbbell test piece was cut out and subjected to a V-notch Charpy impact test in accordance with ISO 179 (2010) using a Tokyo Koki Testing Machine Co., Ltd. C1-4-01 model testing machine. The impact strength (kJ / m 2 ) is calculated.
[0096] <Number average fiber length of carbon fibers contained in molded products> A sample cut from a molded product is heated in air at 500°C for 30 minutes in an electric furnace to thoroughly burn off the thermoplastic resin (A) and compound (B) and separate the carbon fibers. At least 400 of the separated carbon fibers are randomly selected and their lengths are measured to the nearest 1 μm using an optical microscope, and the number average fiber length (Ln) is calculated using the following formula.
[0097] Number average fiber length (Ln) = (ΣLi) / Nf Where: Li: Measured fiber length (i = 1, 2, 3, . . . , n) Nf: Total number of fibers whose fiber length was measured EXAMPLES
[0098] The present invention will be described in detail below based on examples, but the present invention is not limited to these. In particular, evaluations were performed when a specific carbon fiber was applied to a representative thermoplastic resin of only one type, but the present invention does not limit the type of thermoplastic resin. [Example 1] A spinning solution containing a polyacrylonitrile copolymer made of acrylonitrile and itaconic acid was obtained. The obtained spinning solution was once discharged from a spinneret into the air, and a coagulation bath made of an aqueous solution of dimethyl sulfoxide was introduced into the coagulation bath to obtain a coagulation thread by a dry-wet spinning method. The coagulation thread was washed with water, then stretched in warm water at 90°C at a bath draw ratio of 3 times, further applied with a silicone oil agent, dried using a roller heated to a temperature of 160°C, and pressurized steam drawing was performed at a draw ratio of 4 times to obtain a carbon fiber precursor fiber bundle with a single fiber fineness of 1.1 dtex. Next, four of the obtained precursor fiber bundles were combined to obtain a single fiber count of 12,000, and the bundle was heat-treated in an oven at an air atmosphere of 230 to 280°C with a draw ratio of 1 to convert it into a flame-resistant fiber bundle. The obtained flame-retardant fiber bundle was subjected to a twisting treatment to impart a twist of 45 turns / m, and was subjected to a pre-carbonization treatment in a nitrogen atmosphere at a temperature of 300 to 800°C with a draw ratio of 1.0 to obtain a pre-carbonized fiber bundle. Next, the pre-carbonized fiber bundle was subjected to a carbonization treatment under conditions of a draw ratio of 1.02 and a carbonization temperature of 1900°C, and then a carbon fiber bundle was obtained without imparting a sizing agent.
[0099] TEX manufactured by Japan Steel Works, Ltd. -A long fiber reinforced resin pellet manufacturing device equipped with a coating die for the electric wire coating method installed at the tip of a 30α type twin screw extruder (screw diameter 30 mm, L / D = 32) was used, the extruder cylinder temperature was set to 330°C, and a thermoplastic resin, polyphenylene sulfide resin ("TORELINA" (registered trademark) M2888 manufactured by Toray Industries, Inc.) was fed from the main hopper and melt-kneaded at a screw rotation speed of 200 rpm. A solid bisphenol A type epoxy resin ("jER" (registered trademark) 1004AF (E - 2), softening point 97°C) was added to the carbon fiber at an amount adjusted to 8.7 parts by mass per 100 parts by mass of the carbon fiber, and then the composition containing the molten thermoplastic resin was fed to a die opening (diameter 3 mm) for discharging the composition, and the composition was continuously arranged so as to cover the periphery of the carbon fiber. After cooling the resulting strand, it was cut with a cutter to a pellet length of 7 mm to obtain a long fiber pellet. At this time, the take-up speed was adjusted so that the carbon fiber was 30% by mass.
[0100] The long fiber pellets thus obtained were injection molded using an injection molding machine (J110AD manufactured by Japan Steel Works, Ltd.) under the following conditions: injection time: 5 seconds, back pressure: 5 MPa, dwell pressure: 20 MPa, dwell time: 10 seconds, cylinder temperature: 330°C, and mold temperature: 130°C to produce ISO dumbbell test pieces as molded products. Here, the cylinder temperature refers to the temperature of the part of the injection molding machine where the molding material is heated and melted, and the mold temperature refers to the temperature of the mold into which the resin is injected to form a predetermined shape. The obtained test pieces (molded products) were subjected to characteristic evaluation. The evaluation results obtained by the above-mentioned methods are summarized in Table 1.
[0101] [Table 1]
[0102] In Table 1, in each of the terms of formulas (1) to (6), "Yes" means that the relationship of the corresponding formula of each term is satisfied, and "No" means that the relationship of the corresponding formula of each term is not satisfied. [Example 2] The carbon fibers obtained in Example 1 were further heat-treated at 2350° C. in a nitrogen atmosphere with a draw ratio of 1.00 to obtain carbon fibers, and the evaluation was carried out in the same manner as in Example 1, except that the carbon fibers obtained in Example 1 were further heat-treated at 2350° C. in a nitrogen atmosphere with a draw ratio of 1.00 to obtain carbon fibers. [Example 3] The evaluation was carried out in the same manner as in Example 2, except that the draw ratio in the additional heat treatment at 2350°C was changed to 1.02. [Example 4] The evaluation was carried out in the same manner as in Example 1, except that the mass content of the carbon fiber contained in the resin composition was changed to 20 mass %. [Example 5] A twin-screw extruder (TEX-30α, manufactured by The Japan Steel Works, Ltd., L / D=31.5) was used to melt-knead each component by main-feeding polyphenylene sulfide resin and side-feeding the same carbon fiber bundle as in Example 1. The melt-kneading was performed at a cylinder temperature of 290°C, a screw rotation speed of 150 rpm, and a discharge rate of 10 kg / hour. The discharged material was collected and cooled in a water-cooled bath to form strands, and the gut was cut into pellets of 5 mm length.
[0103] The pellets were injection molded using an injection molding machine (J150EII-P manufactured by Japan Steel Works, Ltd.) to produce test pieces for various evaluations. Injection molding was performed at a cylinder temperature of 320°C and a mold temperature of 150°C. The obtained test pieces were annealed at 150°C for 2 hours, air-cooled, and then used for each test. [Comparative Example 1] The evaluation was carried out in the same manner as in Example 1, except that the carbon fiber was changed to "TORAYCA" (registered trademark) T700S-24000-50E manufactured by Toray Industries, Inc. [Comparative Example 2] The evaluation was carried out in the same manner as in Example 1, except that the carbon fiber was changed to "TORAYCA" (registered trademark) M40J-12000-50E manufactured by Toray Industries, Inc. [Comparative Example 3] The evaluation was carried out in the same manner as in Example 1, except that the carbon fiber was changed to "TORAYCA" (registered trademark) M50J-6000-50E manufactured by Toray Industries, Inc. [Comparative Example 4] The evaluation was carried out in the same manner as in Example 1, except that the carbon fiber was changed to "TORAYCA" (registered trademark) M55J-6000-50E manufactured by Toray Industries, Inc. [Comparative Example 5] The evaluation was performed in the same manner as in Example 5, except that the carbon fiber was changed to "TORAYCA" (registered trademark) T700S-24000-50E manufactured by Toray Industries, Inc., and the carbon fiber contained in the resin composition was changed to 30 mass %. [Comparative Example 6] The evaluation was carried out in the same manner as in Example 1, except that the carbon fiber was changed to "TORAYCA" (registered trademark) T800S-24000-10E manufactured by Toray Industries, Inc. [Industrial Applicability]
[0104] The resin composition of the present invention can be widely used for applications such as compounds, pellets, SMC (sheet molding compound), UD (unidirectional) tapes, etc. These intermediate substrates can ultimately be used for various parts and members, and are particularly suitable for electrical and electronic equipment, office automation equipment, home appliances, automotive parts, internal members, and housings.
Claims
1. The resin composition contains carbon fiber and a thermoplastic resin, the carbon fiber having a single fiber diameter of 6.0 μm or more, a tensile modulus E of 350 to 500 GPa, the tensile modulus E (GPa) and the loop breaking load A (N) satisfying the relationship of formula (1), the thermoplastic resin being at least one thermoplastic resin selected from the group consisting of polyolefins, polyamides, polyesters, polycarbonates and polyarylene sulfides, the mass content Wf of the carbon fiber being 15 to 55%, the carbon fiber being composed of carbon fiber bundles having 3,000 to 60,000 filaments, and the twist angle of the surface layers of the carbon fiber bundles being 2.0 to 30.5°. A≧-0.0017×E+1.02...Formula (1)
2. A resin composition comprising carbon fiber and a thermoplastic resin, the carbon fiber has a single fiber diameter of 6.0 μm or more, a crystallization parameter Iv / Ig measured by Raman spectroscopy of 0.65 or less, the crystallization parameter Iv / Ig and the tensile modulus E (GPa) satisfy the relationship of formula (2), the thermoplastic resin is at least one thermoplastic resin selected from the group consisting of polyolefins, polyamides, polyesters, polycarbonates, and polyarylene sulfides, the mass content Wf of the carbon fiber is 15 to 55%, the carbon fiber is composed of carbon fiber bundles having 3,000 to 60,000 filaments, and the twist angle of the surface layers of the carbon fiber bundles is 2.0 to 30.5°. E≧290×(Iv / Ig) -0.23 ・・・Formula (2)
3. The resin composition according to claim 2, wherein the carbon fiber has a crystallization parameter Iv / Ig of 0.40 or more as determined by Raman spectroscopy.
4. The resin composition according to any one of claims 1 to 3, wherein the single fiber compressive strength Fc (GPa) and the crystallite size Lc (nm) of the carbon fiber composite as measured by a compression fragmentation method satisfy the relationship of formula (3). Fc≧1.3×10 / Lc-0.2...Formula (3)
5. The degree of crystal orientation of the carbon fiber is π 002 is 80.0 to 95.0%, the crystallite size Lc is 2.2 to 3.5 nm, and the crystallite size Lc (nm) and the degree of crystal orientation π 002 The resin composition according to any one of claims 1 to 4, wherein (%) satisfies the relationship of formula (4). π 002 ≧ 4.0 × Lc + 73.2 ··· Equation (4)
6. 6. The resin composition according to claim 1, wherein the carbon fiber has a length of 100 mm or more before melt-kneading in the resin composition obtained by melt-kneading the carbon fiber and the thermoplastic resin.
7. 7. The resin composition according to claim 1, wherein the carbon fiber has a heat loss rate of 0.15% or less at 450° C.
8. 8. The resin composition according to claim 1, wherein the carbon fiber has a single fiber diameter of 6.5 to 8.5 μm.
9. A resin composition comprising carbon fiber and a thermoplastic resin, the carbon fiber has a single fiber diameter of 6.0 μm or more, the thermoplastic resin is at least one thermoplastic resin selected from the group consisting of polyolefin, polyamide, polyester, polycarbonate, and polyarylene sulfide, the mass content Wf of the carbon fiber is 15 to 55%, the flexural modulus FM (GPa) of the resin composition, the mass content Wf (%) of the carbon fiber in the resin composition, and the tensile modulus E (GPa) of the carbon fiber satisfy the relationships of formulas (5) and (6), the carbon fiber is composed of carbon fiber bundles having a filament count of 3,000 to 60,000, and the twist angle of the surface layer of the carbon fiber bundles is 2.0 to 30.5°. FM / Wf 0.5 >6.8 ……Formula (5) FM / Wf 0.5 >0.01×E+3.00 ……Formula (6)
10. The resin composition according to claim 9, having a flexural modulus FM of 41 to 55 GPa.
11. A molded article obtained by molding the resin composition according to any one of claims 1 to 10.
Citation Information
Patent Citations
Thermoplastic resin molding and thermoplastic resin composition
JP2006001965A
Flame resistant polymer fiber bundle and method for producing flame resistant fiber bundle
JP2009197358A
Filament body of fiber-reinforced resin and method for producing the same, and electric wire cable using the same and method for manufacturing the same
JP2012097386A
Carbon fiber bundle and production method thereof
JP2014141762A
Resin composition and method for producing the same
JP2017190426A